Pelatihan Kewirausahaan dan Perhitungan Akuntansi Biaya untuk Meningkatkan Ekonomi di Desa Bojongsoang Kabupaten Bandung - Pikir Wisnu Wijayanto; Rochmawati Rochmawati; Rennyta Yusiana (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2022)
Most residents who live in the Bojongsoang Village area, especially in RW 10 Kampung Cijagra, seek income as factory workers, freelancers, and some others sell various community needs or what is known as entrepreneurial activities. People's knowledge of bookkeeping or recording and calculations is still said to be simple, or even bookkeeping and recording are not carried out. Therefore, they do not know the number of business costs undertaken or other incoming and outgoing money used in their transaction processes. They also do not understand the calculation concept in accounting for production costs and the cost of goods manufactured. From these conditions, the Community Service (PkM) team at Telkom University provided training in cost accounting calculations. The activity aimed at the community could be helped in terms of proper entrepreneurship bookkeeping and calculating various basic costs adapted to developing accounting theory. In addition, the understanding of the difference between an entrepreneur and a trader was also provided by the PkM team so that small traders not only become sellers but also become reliable entrepreneurs. Thus, various abilities and opportunities for profit will be better.